The New Testament of Our Lord and Saviour Jesus Christ : Translated from the Latin Vulgate, Diligently Compared with the Original Greek, and First Published by the English College at Rheims, A.D. 1582 - Gibbons, James, Cardenal (prefacio) (The National Catholic War Council)
Edición especial del Nuevo Testamento, según la versión Douay de la Biblia, dirigida especialmente para el ejército y la marina. Su tamaño y el material resistente de sus cubiertas hacen que esta edición sea fácil de llevar consigo.